Оптимізація рецептурного складу та деяких споживчих властивостей гречаних цукерок - Півень, Олена Миколаївна; Демидов, Ігор Миколайович; Мольченко, Світлана Миколаївна; Березка, Тетяна Олександрівна (Національний технічний університет "Харківський політехнічний інститут", 2020)
В роботі встановлено оптимальний рецептурний склад та розроблена технологія виробництва нових видів цукерок Експериментально встановлено кількісне співвідношення кориці, мускатного горіху і чорного перцю у рецептурі гречаних цукерок та отримано рівняння регресії, яке пов’язує склад речовин-факторів у кондитерському виробі, при якому можна було отримати максимальну органолептичну оцінку. Відзначено, що поєднання запропонованих інгредієнтів забезпечує збалансований склад кондитерському виробу, а також відсутність хімічних компонентів у готовому продукті.

Confectionery is an important component in the diet of consumers and is one of the favorite products that are in ever-increasing demand from all walks of life. The main significant disadvantage of confectionery is their low physiological value - they are virtually devoid of such important biologically active substances as vitamins, dietary fiber, minerals and others. Candy is a complex, multi-component product and among all confectionery products stand out for the variety of composition, technology and range of finished products. One of the ways to improve the quality of food is the use of new non-traditional types of plant raw materials that contain a balanced complex of proteins, lipids, minerals, vitamins and have high nutritional, taste and therapeutic properties. Dissemination of the range of healthy products is a priority in the food industry of Ukraine. The research presented in the article is aimed at improving the consumer properties and increasing the nutritional value of sweets in order to improve the diet of the population. The new sweets include: green buckwheat, dates, dried cranberries, cocoa butter, coconut flakes, honey, peanuts, nutmeg, cinnamon, black pepper, waffle crumbs (for decoration). The main recipe component is the kernel of green buckwheat, germinated and dried by a special technology that allows you to save all the nutrients and trace elements. The optimal recipe composition and technology of production of new types of candies are established. The quantitative ratio of cinnamon, nutmeg and black pepper in the recipe of buckwheat candies is experimentally established and the regression equation organoleptic evaluation. It is noted that the combination of the proposed ingredients provides a balanced composition of the confectionery product, as well as the absence of chemical components in the finished product. Such sweets are recommended for people who lead a healthy lifestyle, play sports, control their weight and anyone who wants to strengthen the immune system.
Optimization of recipe composition and some consumer properties of buckwheat candies
Keywords: горіхи; прянощі; якість; органолептичні властивості; nuts; spices; quality; organoleptic properties